Docosahexaenoic acid prevents palmitate‐induced insulin‐dependent impairments of neuronal health. Issue 3 (6th February 2020) - Loehfelm, Aline; Elder, Megan K.; Boucsein, Alisa; Jones, Peter P.; Williams, Joanna M.; Tups, Alexander
Abstract: The importance of fatty acids (FAs) for healthy brain development and function has become more evident in the past decades. However, most studies focus on the hypothalamus as an important FA‐sensing brain region involved in energy homeostasis. Less work has been done to evaluate the effects of FAs on brain regions such as the hippocampus or cortex, two important centres of learning, memory formation, and cognition. Furthermore, the mechanisms of how FAs modulate the neuronal development and function are incompletely understood. Therefore, this study examined the effects of the saturated FA palmitic acid (PA) and the polyunsaturated FA docosahexaenoic acid (DHA) on primary hippocampal and cortical cultures isolated from P0/P1 Sprague Dawley rat pups. Exposure to PA, but not DHA, resulted in severe morphological changes in primary neurons such as cell body swelling, axonal and dendritic blebbing, and a reduction in synaptic innervation, compromising healthy cell function and excitability. Pharmacological assessment revealed that the PA‐mediated alterations were caused by overactivation of neuronal insulin signaling, demonstrated by insulin stimulation and phosphoinositide 3‐kinase inhibition. Remarkably, co‐exposure to DHA prevented all PA‐induced morphological changes. This work provides new insights into how FAs can affect the cytoskeletal rearrangements and neuronal function via modulation of insulin signaling.